PP.27.27: INFLAMMATION AND ARTERIAL STIFFNESS BIOMARKERS. (June 2015) - Huguet, E.; Manccanelli, G.; Pardini, P.; Vigna, L.; Obregon, S.; Haehnel, M.; Brandani, L.; Carrizo, P.; Castellaro, C.; Koretzky, M.; Dulude, E. Perasso; Vaisbuj, F.; et al.
Abstract : Objective: Recent studies have shown a strong predictive value of Neutrophil-Lymphocyte Ratio (NLR) for the risk of coronary heart disease. Higher values of NLR are useful to reclassify arteriosclerotic risk in subjects at low CV risk. On the other hand, high-sensitivity C-Reactive Protein (hsCRP) has been widely linked to cardiovascular inflammation. Based on this, our aim was to evaluate NLR and hsCRP's efficacy to identify the risk of arterial stiffness in subjects at low risk but with an active inflammatory response. Design and method: We included a cohort of 108 normotensive subjects (51 ± 10.8 years, 45% female) who consecutively attended for the study of their global cardiovascular risk. NLR, hsCRP and arterial stiffness were assessed and two groups were identified; 1) Group PWV < 10 m/sec (G1), 2) Group PWV > o = 10m/sec (G2). Results: After applying exclusion criteria our final sample was 40 subjects, 42% female, BMI 26.2 ± 4.2. Among higher values of hsCRP a strong efficacy to identify an increased PWV (G1: 0.72 ± 0.43 versus G2: 1.34 ± 0.9 < 0.0001) was found. Association between NLR and PWV was also highly significant (G1: 0.9 ± 0.4 vs G2: 2.6 ± 0.7), and a continuous direct association between their values in the last tertile of G1 was found. PWV was closely linked to age, BMI and SBP, while the hsCRP proved its predictive value independent of these variables. Conclusions: NLR and hsCRP showed predictive value for the risk of arterial stiffness in normotensive subjects at low CV risk. This association was observed continuously with progressive values of PWV. It is an accessible, low cost determination in daily clinical practice, and it should be reevaluated in larger cohorts to determine their applicability in screening and risk stratification as affordable biomarkers which can represent early CV risk in low risk subjects.